Business Continuity Plan as an Effort to Mitigate Risk in the Implementation of Kogartap I/Jakarta Tasks in the Jakarta Region - Irma Dwi Mulyanti (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2026)
Kogartap I/Jakarta plays a strategic role in maintaining order in the capital city, executing state ceremonial duties, and supporting both military and non-military operations. In carrying out these tasks, the unit faces a number of potential risks, both internal—such as disruptions in communication and logistics systems—and external, including natural disasters, security threats, or social crises. As a result, the implementation of a Business Continuity Plan (BCP) is critically important as a risk mitigation strategy aimed at ensuring the organization's functionality during operational disruptions. This study seeks to analyze the extent to which BCP can be effectively applied within Kogartap I/Jakarta, and how it contributes to enhancing the organization’s readiness and responsiveness in crisis situations. The research employs a descriptive qualitative approach, using data collection techniques such as interviews, observation, and document analysis. It is expected that this study will strengthen BCP system recommendations to ensure operational continuity and the sustainability of routine garrison tasks in achieving the unit’s operational and strategic objectives.